Increasing The Engagement Of 10th-Grade Culinary Students Through The Implementation Of Game-Based Learning Using Word Search - Daud Arzaky Ahmad; Laili Hidayati (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of interactive learning using a word search game to increase student participation in the Culinary Vocational Program at SMK Negeri 2 Malang. Low student activity in conventional, teacher-centered instruction prompted the adoption of a more interactive approach. A game‑based learning model was chosen for its potential to enhance motivation, engagement, and learning outcomes among students in the culinary program at SMK Negeri 2 Malang. The research employed a descriptive qualitative approach through observation, interviews, and documentation. Data were analyzed using the following steps: (1) data reduction, (2) data display, and (3) drawing conclusions/verification. Conclusions were drawn by comparing field findings with relevant theory. Observations and interviews indicated a tendency for the percentage of students willing to come forward and answer to increase from 30% to approximately 70% when using the word search. Students also reported improved focus and greater enthusiasm for basic culinary skills material. The study concludes that the word search is a feasible alternative as an innovative instructional medium suited to the characteristics of vocational education, being easy to implement, relevant to core program content, and effective in promoting active student engagement.